PENGARUH INFLASI, SUKU BUNGA BANK INDONESIA, HARGA MINYAK DUNIA DAN CADANGAN DEVISA TERHADAP INDEKS HARGA SAHAM GABUNGAN - Msy Mikial (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
This research aims to know influence of Inflation, BI Interest Rate, World Oil Price and Foreign Exchange Reserves to Composite Stock Price Index at Indonesia Stock Exchange (IDX)Raised hypothesis “ There are positive influence of Inflation, BI Interest Rate, World Oil Price and Foreign Exchange Reserves to Composite Stock Price Index. The results showed that Inflation, BI Interest Rates, World Oil Prices, and Foreign Exchange Reserves affect the Composite Stock Price Index (CSPI). 51.03% of Composite Stock Price Index (CSPI) influenced by inflation, Bank Indonesia interest rates, oil prices, and foreign exchange reserves, while the remaining 48.97% influenced by other factors not examined. From the analysis of partial turns all variables significantly influence the level of the Composite Stock Price Index (CSPI), and the most dominant influence is inflation, whereas the smallest effect is the BI interest rate. Key Word : Inflation, BI Interest Rate, World Oil Price, Foreign Exchange Reserves, Composite Stock Price Index